2015
DOI: 10.1016/j.bbrc.2015.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Punicalagin exerts protective effect against high glucose-induced cellular stress and neural tube defects

Abstract: Maternal diabetes-induced birth defects remain a significant health problem. Studying the effect of natural compounds with antioxidant properties and minimal toxicities on diabetic embryopathy may lead to the development of new and safe dietary supplements. Punicalagin is a primary polyphenol found in pomegranate juice, which possesses antioxidant, anti-inflammatory and anti-tumorigenic properties, suggesting a protective effect of punicalagin on diabetic embryopathy. Here, we examined whether punicalagin coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 38 publications
2
26
1
1
Order By: Relevance
“…We demonstrated that PUN pretreatment increased antioxidant enzyme SOD activity and reduced MDA formation following MI/R. These results indicate that PUN suppresses MI/R-induced oxidative stress, which is similar to previous studies that PUN attenuates oxidative stress in other diseases (Zhong et al, 2015;Rao et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…We demonstrated that PUN pretreatment increased antioxidant enzyme SOD activity and reduced MDA formation following MI/R. These results indicate that PUN suppresses MI/R-induced oxidative stress, which is similar to previous studies that PUN attenuates oxidative stress in other diseases (Zhong et al, 2015;Rao et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…30,31,37,49,77 However, the effectiveness of these natural compounds needs be tested in human diabetic pregnancies.…”
Section: Commentmentioning
confidence: 99%
“…30,31 Epigallocatechin gallate is the major polyphenol in green tea ( Camellia sinensis ) and makes up to approximately 30% of the solids in green tea. 32 …”
mentioning
confidence: 99%
“…We have demonstrated that oxidative stress plays a causal role in PGDM-induced neural tube defects [1214,16,49,58,6063,67] and CHDs [48,50,52,57], and that overexpression of SOD1 in transgenic mice ameliorates PGDM-induced CHDs [48,50]. We previously reported that PGDM in vivo and high glucose in vitro decreased the expression of miR-322 in E8.5 embryos, and that overexpressing SOD1 restores miR-322 levels [19].…”
Section: Discussionmentioning
confidence: 99%